(untitled) (Journal of NELTA, 2018)
The present article discusses new varieties of English with reference to intelligibility and comprehensibility. It has been observed that new varieties of English display deviant phonological features. Speakers of these varieties insert a sound, delete a sound, substitute a sound, and rearrange sounds when they pronounce certain words. Moreover, they use deviant word stress patterns. These things affect the intelligibility of their speech. The new varieties differ at the level of discourse as well; the content and language used to perform certain speech acts such as coaxing, responding to questions, etc., may result in miscommunication. Thus, unintelligibility is a result of mother tongue interference and incomprehensibility is a result of mother culture interference. The article illustrates unintelligibility and incomprehensibility using examples from non-native varieties of English.